Effects of dezocine for the prevention of postoperative catheter-related bladder discomfort: a prospective randomized trial - Zhang GF; Guo J; Qiu LL; Li SM; Zheng M; Xia JY; Yang JJ (Dove Medical Press, 2019)
Guang-Fen Zhang,1 Jie Guo,2 Li-Li Qiu,1 Shu-Ming Li,1 Man Zheng,2 Jiang-Yan Xia,1 Jian-Jun Yang1,31Department of Anesthesiology, Zhongda Hospital, School of Medicine, Southeast University, Nanjing, Jiangsu, People’s Republic of China; 2Department of Anesthesiology, Affiliated Hospital of Nanjing University of Traditional Chinese Medicine, Nanjing, Jiangsu, People’s Republic of China; 3Department of Anesthesiology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of ChinaPurpose: To evaluate the effects of dezocine on the prevention of postoperative catheter-related bladder discomfort (CRBD).Patients and methods: Ninety-six adult patients undergoing abdominal surgery with urinary catheterization under general anesthesia were randomized into dezocine and control (flurbiprofen) groups. The postoperative CRBD, pain score, sedation score and adverse effects were evaluated at 0, 1, 2 and 6 hrs after tracheal extubation.Results: The primary outcome showed a lower incidence of CRBD at 1 hr post-extubation in the dezocine group (29.17%) than the control group (58.33%, P<0.01). The incidences at 0 and 2 hrs post-extubation and the overall incidence were also lower in the dezocine group than the control group (all P<0.05). The severity of CRBD at 0, 1, 2 and 6 hrs and the pain, sedation score and other adverse effects were comparable between the two groups (P>0.05); however, the overall severity of CRBD was decreased in the dezocine group compared with the control group (P<0.05).Conclusion: Intraoperative dezocine reduces the incidence and severity of postoperative CRBD without clinically relevant adverse effects.Keywords: dezocine, catheter-related bladder discomfort, general anesthesia, postoperation